An Analysis of Grammatical Errors Recount Text Written by Malahayati University Students - Rahmawati, Hamida Nur; Mar’an, Desy Awal (CV. Tripe Konsultan, 2025)
This study examined grammatical errors in recount texts written by 20 Management students at Malahayati University. Using a qualitative descriptive approach, the analysis focused on vocabulary, mechanics, organization, grammar, and content. The results showed that while some students demonstrated good writing ability, many struggled, particularly with grammar and mechanics. Weaknesses were evident in verb tense usage, subject–verb agreement, and sentence structure, as well as in punctuation and capitalization. Differences in vocabulary and organization scores indicated varying levels of skill in word choice and text structuring. The findings highlight the need for targeted instructional strategies, especially grammar-focused lessons, explicit training in mechanics, and individualized support for vocabulary building and organizational skills. Identifying recurring error patterns allows for more effective teaching interventions aimed at improving students’ proficiency in recount writing.